On the Marginal Deformations of General (0,2) Non-Linear Sigma-Models - Adam, Ido [UNESP]; Donagi, R.; Katz, S.; Klemm, A.; Morrison, D. R. (Amer Mathematical Soc, 2015)
In this note we explore the possible marginal deformations of general (0,2) non-linear sigma-models, which arise as descriptions of the weakly coupled (large radius) limits of four-dimensional N = 1 compactifications of the heterotic string, to lowest order in alpha' and first order in conformal perturbation theory. The results shed light from the world-sheet perspective on the classical moduli space of such compactifications. This is a contribution to the proceedings of String-Math 2012.
Keywords: Sigma models; conformal field models in string theory; flux compactifications